Answer:
B (2.5, 0)
Step-by-step explanation:
2x - y = 5 (multiply all by 4)
8x- 4y = 20
-8x - 4y = - 20
eliminate the 4y
8x- 4y = 20
-8x - 4y = - 20
-------------------- –
16x = 40
x = 40/16 = 2.5
now we substitute x with 2.5
2x - y = 5
2(2.5) - y = 5
y = 0
Answer:
The answer is
Step-by-step explanation:
The line of g(x) is steeper and has a lower y-intercept
:)
That’s the answer <3
Answer:
(f + g)(3) = 9
Step-by-step explanation:
Given:
f(x) = x² + 1
g(x) = x - 4
Required:
(f + g)(3)
SOLUTION:
✔️Find f(3) by substituting x = 3 into f(x) = x² + 1:
f(3) = (3)² + 1 = 9 + 1
f(3) = 10
✔️Find g(3) by substituting x = 3 into g(x) = x - 4:
g(3) = 3 - 4
g(3) = -1
✔️Find (f + g)(3):
(f + g)(3) = f(3) + g(3)
= 10 + (-1)
= 10 - 1
(f + g)(3) = 9
Is it not zero ???? ? ? ?